Війти Стародубського магістрату (друга половина ХVІІ – ХVІІІ ст.) - Доманова, Г. (Сiверянський лiтопис, 2016)
Привілеї на маґдебурзьке право містам Чернігово-Сіверщини зобов’язували міщанську спільноту формувати органи міського самоврядування на чолі з війтом. У статті
зроблена спроба реконструювати персональний склад війтівського уряду Стародубського магістрату впродовж другої половини ХVІІ – ХVІІІ ст. та проаналізувати
проблему взаємовідносин урядовців магістрату з представниками козацької старшини
під час обрання міського голови. Привилегии на Магдебургское право городам Чернигово-Сиверщины обязывали
мещанство формировать органы местного самоуправления во главе с войтом. В
статье осуществлена попытка реконструировать персональный состав войтовской
должности Стародубского магистрата во второй половине ХVІІ – XVІІІ веках и
проанализировать проблему взаимоотношений должностных лиц магистрата с представителями казацкой старшины во время избрания городского главы. The privileges of the Magdeburg Law in the cities of Chernihiv-Sivershchyna obliged
middle-class community to form the municipal governments headed by viit. After the Ukrainian
national revolution of the mid XVII century and Ukraine’s accession to Russia middle-class
community tried to keep status quo. On this basis the understanding with both the Hetman
and the tsarist governments was reached. The head of the municipal government – the viit
was elected by citizens on a competitive basis with a subsequent Hetman’s approval. His
responsibilities included the management of administration and courts.
The article attempts to reconstruct the personnel of the viit government of Starodub
magistrate during the second half of the XVII – XVIII centuries and analyze the problem
of relationship between the magistrate officials and representatives of Cossacks’ sergeant
majors at the time of election of the mayor.
Therefore, in Starodub during the second half of the XVII – XVIII centuries more than
11 people occupied the viit post and the elections of the mayor in the XVIII century were
accompanied by active struggle for power.